1999
DOI: 10.1039/a904718b
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of thiocarboxylates: syntheses and characterization of silver and copper thiocarboxylate complexes, and the structures of [Ph4P][M(SC{O}Me)2] (M = Cu or Ag) and [Et3NH][Ag(SC{O}Ph)2]

Abstract: The bis(thiocarboxylate) complexes of silver() and copper() namely, [Ph 4 P][M(SC{O}Me) 2 ], (M = Cu 1 or Ag 2) and [Et 3 NH][M(SC{O}Ph) 2 ] (M = Cu 3 or Ag 4) were prepared from the appropriate metal salt, RC{O}S Ϫ anions and the counter ion in the ratio 1 : 2 : 1. The structures of 1, 2 and 4 were determined by X-ray crystallography. The compounds 1 and 2 are isomorphous and isostructural. In both structures, the metal is bonded to sulfur atoms of two thioacetate ligands to give a near-linear geometry. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…The Cu(1)Á Á ÁCu(2) distance, 2.6311(8) A ˚, observed here is similar to 2.62 A ˚in [(Ph 3 P)Cu(m-SC{O}Ph) 2 Cu(PPh 3 ) 2 ] 4 and shorter than the sum of the van der Waals radii of Cu(I), 2.8 A ˚.26 Further, the two p-methylbenzenecarboselenoato ligands adopt anti stereochemistry in the Cu 2 Se 2 ring. The C-C{=O}Se plane and the benzene ring are twisted by 3.8(4) and 9.0(3) in the two ligands which are very normal 3,5,6. The structure of 2 in general is quite similar to the sulfur analogue [(Ph 3 P)Cu(m-SC{O}Ph) 2 Cu(PPh 3 ) 2 ] 4 reported by Speier et al…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…The Cu(1)Á Á ÁCu(2) distance, 2.6311(8) A ˚, observed here is similar to 2.62 A ˚in [(Ph 3 P)Cu(m-SC{O}Ph) 2 Cu(PPh 3 ) 2 ] 4 and shorter than the sum of the van der Waals radii of Cu(I), 2.8 A ˚.26 Further, the two p-methylbenzenecarboselenoato ligands adopt anti stereochemistry in the Cu 2 Se 2 ring. The C-C{=O}Se plane and the benzene ring are twisted by 3.8(4) and 9.0(3) in the two ligands which are very normal 3,5,6. The structure of 2 in general is quite similar to the sulfur analogue [(Ph 3 P)Cu(m-SC{O}Ph) 2 Cu(PPh 3 ) 2 ] 4 reported by Speier et al…”
mentioning
confidence: 58%
“…For instance, a number of thiocarboxylate metal complexes have been synthesized and well characterized. [1][2][3][4][5][6] Some of them have been shown to be good single source precursors for sulfide materials. 1,2 For copper thiocarboxylate, Speier et al first reported a triphenylphosphine adduct of a Cu(I) thiocarboxylate complex with an unsymmetrical dimeric structure 4 in 1991.…”
Section: Introductionmentioning
confidence: 99%
“…This is a common feature observed in various thiobenzoate complexes. 26,[31][32][33][34][35][36][37][38] Thermal properties of compounds 1-5…”
Section: Description Of the Molecular Structure Ofmentioning
confidence: 99%
“…2.798, 2.806, 2.867, 2.884(2) A ˚), the explanation may be more conveniently found to originate further afield in interactions of the NH hydrogen atoms pairwise with nearby sulfate groups, thus: Examples of copper(I) linearly coordinated by a pair of unidentate thio ligands are surprisingly sparse, the present seemingly the first example of its type. Comparison may be made with the [Cu(S•CO•Ph) 2 ]species, 20 wherein Cu-S are 2.151(3) A ˚, S-Cu-S 176.6(2) • , [Cu(SAd) 2 ] -(Ad ∫ adamantanyl) Cu-S 2.147(1) A ˚, S-Cu-S 180 • 21 and, in a bis(S-dithiocarbamyl) environment, Cu-X 2.163(9) A ˚, S-Cu-S 180 • , 22 all essentially harmonious with the present.…”
Section: X-ray Structuresmentioning
confidence: 99%